2019
DOI: 10.3390/v11090777
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mammalian orthorubulavirus 5 Discovered as Accidental Cell Culture Contaminant

Abstract: A distinct Russian Mammalian orthorubulavirus 5 (PIV5) was detected in cell culture exhibiting cytopathic effect and hypothesized to be contaminated by a scientist with respiratory symptoms. The identification of the divergent strain indicated a lack of knowledge on the diversity of PIV5 strains and calls for surveillance of global PIV5 strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…VSV is frequently used as an experimental tool, for example, as a pseudotype virus ( 40 ). Previous studies have also reported possible contamination of PIV5 in cultured cells ( 41 , 42 ). Additionally, it has been reported that KDV RNA might be a contaminant in the nucleic acid extraction kit ( 43 ).…”
Section: Discussionmentioning
confidence: 90%
“…VSV is frequently used as an experimental tool, for example, as a pseudotype virus ( 40 ). Previous studies have also reported possible contamination of PIV5 in cultured cells ( 41 , 42 ). Additionally, it has been reported that KDV RNA might be a contaminant in the nucleic acid extraction kit ( 43 ).…”
Section: Discussionmentioning
confidence: 90%
“…These changes are similar to those caused by other animal PIV5 strains (Liu et al., 2015, 2017). It is also clear that the true genetic diversity of PIV5 may be greater than that first realized (Feehan et al., 2019), meaning that low‐level PIV5 circulation in ticks remains a potential risk of infection transmission to humans.…”
Section: Discussionmentioning
confidence: 99%
“…VSV is frequently used as an experimental tools; for example, as a pseudotype virus (43). Additionally, previous studies have reported possible contamination of PIV5 in cultured cells (44,45). Therefore, we excluded these viral infections to avoid counting false positives.…”
Section: Discussionmentioning
confidence: 99%